Echo Analysis in Iberian Bullfighting Arenas Through Objective Parameters and Acoustic Simulation - Sara Girón; Manuel Martín-Castizo; Miguel Galindo (Applied Sciences)
The existence of echoes in an acoustic event can ruin the capture of a spoken message and the perception of a piece of music. Likewise, in the performers’ area, clear hearing is essential for the coordination and execution of the ensemble. Bullrings are buildings with a circular plan in which echo-encouraging focalisations can occur. Since bullrings lack a roof, the density of reflections is lower than that in a closed area, and therefore strong isolated reflections perceived by the audience as an echo can be created. In this work, calculations of the echo parameter (Echo Criterion EK) and inspection of impulse responses and energy decay curves are obtained in an on-site measurement campaign in the audience zones and in arena areas where the EK parameter exceeds the thresholds. To this end, four bullrings very emblematic of the Iberian Peninsula together with a very prominent Roman amphitheatre in a relatively good state of conservation in the Roman province of Hispania comprise the study cases. Experimental results of the EK parameter and from acoustic simulation in two of the bullrings present good concordance and show that there is no echo for music in any of the venues in the spectator zones and that the most critical area is when source and receiver are both in the arena, where even double and triple echoes appear.